Macro Effects of Capital Requirements and Macroprudential Policy - Q. Farooq Akram (Norges Bank, 2012)
I investigate macro effects of higher bank capital requirements on the Norwegian economy and their use as a macroprudential policy instrument under Basel III. To this end, I develop a macroeconometric model where the capital adequacy ratio, lending rates, asset prices and credit interact with each other and with the real economy. The empirical results suggest that changes in capital requirements are primarily transmitted via lending rates to the other variables in the model. The proposed increases in capital requirements under Basel III are found to have significant effects especially on house prices and credit. I also derive optimal paths for the countercyclical capital buffer in response to various shocks. The buffer is found to equal its imposed ceiling of 2.5% in response to most of the shocks considered while its duration varies in the range of 1-12 quarters depending on the shock and its persistence.
hdl:11250/2496815
Keywords: C52; C53; E52; G38; 330; Basel III; capital requirements; macroprudential policy